Co-Production of KPC-2 and NDM-5 in a Carbapenem-Resistant Klebsiella Pneumoniae Clinical Isolate: Genetic Insights and Risks - Xia Y; Zhou P; Gao H; Wu X; Zhou Y; Han W; Wan C; Wu Q; Ding J; Yu F (Infection and Drug Resistance)
Yuanzhi Xia,1,* Peiyao Zhou,2,* Haojin Gao,2,* Xiaocui Wu,2 Ying Zhou,2 Weihua Han,2 Cailing Wan,2 Qiong Wu,1 Jiawei Ding,3 Fangyou Yu2 1Department of Clinical Laboratory, The Second Affiliated Hospital of Xiamen Medical College, Xiamen, Fujian, People’s Republic of China; 2Department of Clinical Laboratory, Shanghai Pulmonary Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 3Department of Medical Laboratory, Yan’an Hospital of Kunming City, Kunming, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fangyou Yu, Email wzjxyfy@163.com Jiawei Ding, Email dingjiaweiyayy@163.comBackground: Carbapenem-resistant Klebsiella pneumoniae (CRKP), particularly strains co-producing KPC and NDM carbapenemases, poses a severe global health threat due to limited treatment options. Understanding the genetic drivers of resistance and transmission is critical.Methods: A multidrug-resistant CRKP strain, KP3T58, co-harboring blaKPC-2 and blaNDM-5, was isolated from an ICU patient. Whole-genome sequencing and comparative genomic analyses were performed. Plasmid transferability was assessed via conjugation assays using E. coli EC600 as the recipient. Virulence phenotypes were evaluated through siderophore production (CAS assay), capsule quantification (uronic acid), serum resistance, and Galleria mellonella infection models. Antimicrobial susceptibility was determined (Vitek-2; CLSI/EUCAST standards).Results: KP3T58 exhibited resistance to nearly all antibiotics except polymyxin. The strain’s multidrug-resistant (MDR) phenotype resulted from a combination of chromosomal mutations and the multiple plasmid-borne resistance genes. Whole-genome analysis identified three key plasmids: a conjugative plasmid pKP3T58_1 (IncFIB/FII/R type, carrying a large resistance gene cluster); a conjugative plasmid pKP3T58_2 (IncI1-I type, high-frequency transfer, carrying blaNDM-5); and a non-conjugative plasmid pKP3T58_3 (IncFII type, carrying blaKPC-2). Conjugation assays confirmed that pKP3T58_1 and pKP3T58_2 could transfer individually or jointly to E. coli EC600, while pKP3T58_3 (retaining only a partial T4SS) could co-transfer to recipient cells with the assistance of pKP3T58_2. MLST confirmed clonal persistence of the high-risk ST11 lineage within the patient. Phylogenetic analysis revealed KP3T58’s clustering within a dominant epidemic ST11-KL64 subclade prevalent in China. Multiple virulence assays (including siderophore production, capsule quantification, serum resistance, and Galleria mellonella infection models) demonstrated that KP3T58 lacks a typical hypervirulent phenotype but retains a certain level of pathogenicity.Conclusion: This study demonstrates clonal evolution of ST11 CRKP to co-produce KPC-2 and NDM-5 within a host, clustering within a prevalent epidemic lineage. Critically, we provide experimental evidence that mobilizable plasmids retaining only a partial T4SS can undergo horizontal transfer when assisted by conjugative plasmids, fundamentally expanding our understanding of resistance dissemination. The convergence of high-risk epidemiology, MDR, and novel plasmid transfer mechanisms in strains like KP3T58 necessitates enhanced surveillance and urgent molecular investigation into the transmission dynamics of these threats.Keywords: Klebsiella pneumoniae, KPC-2, NDM-5, carbapenemases, ST11